Implementation of the Interactive E-LKPD for Biotechnology Materials with the Argument-Driven Inquiry (ADI) Model Oriented to Improving the Argumentation Ability of Middle School Students - Hasnunidah, Neni; Utami, Tri; Abdurrahman, Abdurrahman; Diawati, Chansyanah (Universitas Negeri Semarang, 2022)
This study aims to describe the effect of implementing interactive e-LKPD on biotechnology materials with the Argument-Driven Inquiry in improving argumentation skills. This study involved 60 grade IX students in a public junior high school in South Lampung, Lampung Province. Quantitative method with non-equivalence pretest-posttest control group has been applied with 30 students in the experimental class and 30 students in the control class. Students in the experimental class get learning assisted by interactive biotechnology e-LKPD with the Argument-Driven Inquiry, while students in the control class are taught using Discovery Learning. The results showed that students who were taught using the Argument Driven Inquiry had N-Gain (g= 0.63) than students in the Discovery Learning (g= 0.28). Furthermore, the effectiveness of biotechnology learning using the Argument-Driven Inquiry shows a high category (ES = 0.90). This shows that the interactive e-LKPD with the Argument-Driven Inquiry effective for improving argumentation skills.